1991
DOI: 10.1163/156854291x00379
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature On Larval Fishes

Abstract: The influence of temperature on fish eggs and larvae is briefly described from an autecological viewpoint. Temperature may have lethal or sub-lethal effects as well as pacing metabolism, other physiological responses and behaviour. It influences body size, growth, differentiation of muscle and meristic characters. Increase of temperature, as would occur with global warming, will change the timing of ecological events such as the spring plankton outburst so influencing the match or mismatch of larvae with their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
240
0
16

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(265 citation statements)
references
References 0 publications
9
240
0
16
Order By: Relevance
“…The second is that temperature in early life affects body shape (Georgakopoulou et al 2007; personal unpublished results) and meristic count (Blaxter 1991;Georgakopoulou et al 2007; personal unpublished results). Georgakopoulou et al (2007), concluded that European sea bass juveniles reared in 15°C had more slender bodies than the ones reared in 20°C, a fact that could explain the higher swimming performance of the former as observed by Koumoundouros et al (2009).…”
Section: Discussionmentioning
confidence: 99%
“…The second is that temperature in early life affects body shape (Georgakopoulou et al 2007; personal unpublished results) and meristic count (Blaxter 1991;Georgakopoulou et al 2007; personal unpublished results). Georgakopoulou et al (2007), concluded that European sea bass juveniles reared in 15°C had more slender bodies than the ones reared in 20°C, a fact that could explain the higher swimming performance of the former as observed by Koumoundouros et al (2009).…”
Section: Discussionmentioning
confidence: 99%
“…Larval size at hatch is generally influenced by incubation temperature (Chambers 1997;Blaxter 1992) and larval length at hatch is an important parameter which influences initial locomotion performances such as swimming speed, escape response and predator avoidance (Blaxter 1992). However, in some cases larger larvae experienced higher vulnerability to predation pressure compared to conspecifics at the same age with smaller body size (Litvak and Leggett 1992).…”
Section: Larval Phasementioning
confidence: 99%
“…This event coincided well with mouth gap opening (this study ;Alshuth 1988;Shields 1989). A functional visual system is also a prerequisite for successful feeding and improved predator avoidance (Blaxter 1992;Fuiman 2002). This ontogenetic event is positively related to increasing temperature.…”
Section: Larval Phasementioning
confidence: 99%
See 1 more Smart Citation
“…However, at one temperature the final mass may owe more to hypertrophy, at another temperature it may owe more to hyperplasia. Curiously, however, in the four species investigated so far temperature exerted opposite effects of muscle growth in the embryos (Blaxter, 1992): in plaice Pleuronectes platessa L., and herring Clupea harengus L. the lower temperature stimulated hypertrophy, the higher temperature hyperplasia, whereas in salmon Salmon salar L. and whitefish, the object of the present study, the opposite was the case (Fig. 4).…”
Section: Discussionmentioning
confidence: 48%